Implementasi Muatan Lokal (Mulok) pada Pembelajaran Terpadu Tematik di TK Pembina Negeri III - Andya Rahmadanti Saputri; Naila Naila; Anisa Sriwahyuni; Winda Sherly Utami; Annisha Erdaliameta (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aimed to describe the implementation of integrated thematic learning based on local content at TK Negeri Pembina III Jambi City. The focus of the study included learning planning, implementation, evaluation, challenges, and the impact of local content-based learning on children's development. The study employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation involving the principal and teachers as research participants. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that integrated thematic learning based on local content had been incorporated into learning themes through the introduction of local foods, Jambi batik, and traditional games. The learning process was carried out through activities that actively engaged children, creating meaningful and concrete learning experiences. Learning evaluation was conducted using observation, anecdotal records, developmental checklists, and portfolios. Several challenges were identified, including limited local culture-based learning media, restricted utilization of the surrounding environment as a learning resource, and the influence of technological developments on children's interest in local culture. The implementation of integrated thematic learning based on local content had positive impacts on children's activeness, creativity, social skills, and cultural understanding. Therefore, the development of local content-based learning should be continuously enhanced through the provision of adequate learning resources and the strengthening of teachers' competencies in integrating local culture into learning activities